1997
DOI: 10.1577/1548-8667(1997)009<0144:eowcse>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Waterborne Copper Sulfate Exposure on Copper Content in Liver and Axial Muscle of Channel Catfish

Abstract: Adult channel catfish Ictalurus punctatus were continuously exposed to waterborne copper sulfate added at concentrations of 1.7, 2 .7, or 3 .6 mg/L for 10 weeks . Overall, there were no significant differences in the copper content of channel catfish axial muscle during the exposure period, and no significant copper accumulation resulted from exposure . Significantly higher concentrations of copper were present in liver tissue of catfish in all exposed groups 2 weeks after exposure to waterborne copper sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Ten millilitre samples were collected and filtered through 0.45 μm pore size nylon filters and acidified to 1% with nitric acid for later analysis for copper content. Copper concentrations in water samples were assayed by graphite furnace atomic absorption spectrometry as previously reported by Griffin et al. (1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten millilitre samples were collected and filtered through 0.45 μm pore size nylon filters and acidified to 1% with nitric acid for later analysis for copper content. Copper concentrations in water samples were assayed by graphite furnace atomic absorption spectrometry as previously reported by Griffin et al. (1997).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to high levels of copper can result in toxic effects, even death, in channel catfish (Straus & Tucker 1993; Wurts & Perschbacher 1994). Earlier studies have shown that though copper may be accumulated in liver tissues but not in axial muscle of catfish exposed to commonly used levels of copper sulphate (Griffin, Hobbs, Gollon, Schlenk, Kadlubar & Brand 1997), the accompanying stress may be relatively mild (Griffin, Davis & Schlenk 1999; Schlenk, Davis & Griffin 1999). When channel catfish were exposed to concentrations similar to those used for disease control, few significant changes were observed in traditional stress indicators; i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To put the observed copper concentrations in fillets in perspective, concentrations in fillets were less than the US Environmental Protection Agency drinking water standard of 1.3 ppm of copper (Boyd ). Further evidence that copper use in aquaculture does not contaminate fish fillets was provided by Griffin et al (). The edible meat from channel catfish in that study did not differ in copper concentration between fish exposed to 3.6 mg/L copper sulfate for 10 wk and control fish.…”
Section: Resultsmentioning
confidence: 99%
“…Channel Catfish Ictalurus punctatus did not accumulate copper in axial muscle when exposed to copper sulfate up to 3.6 mg/L (0.9 mg/L Cu) for 10 weeks, indicating that copper use for cultured Channel Catfish should not pose any hazard to the human consumer (Griffin et al. 1997). Furthermore, about 62% of copper is converted to particulate forms and transported to the sediment within 9.4 d after dosing.…”
Section: Discussionmentioning
confidence: 99%